Antimicrobial susceptibilities of Neisseria gonorrhoeae strains isolated in Surabaya, Indonesia. - Joesoef, M R (1994)
Until recently, the only common strains of antimicrobial agent-resistant Neisseria gonorrhoeae detected in Indonesia were penicillinase-producing N. gonorrhoeae (PPNG) strains. Despite the spread of resistance to other antimicrobial agents among N. gonorrhoeae in Southeast Asia, surveillance for such resistance in Indonesia has been limited. We evaluated the in vitro susceptibilities of 86 N. gonorrhoeae isolates from female sex workers in Surabaya, Indonesia, to 13 antimicrobial agents. Of the 86 isolates, 89% were resistant to penicillin (MIC, > or = 2.0 micrograms/ml), 98% were resistant to tetracycline (MIC, > or = 2.0 micrograms/ml), 18.1% were resistant to spectinomycin (MIC, > or = 128.0 micrograms/ml), and 97.7% showed decreased susceptibility to thiamphenicol (MIC, 1 to 2 micrograms/ml). Thus, thiamphenicol and spectinomycin may be approaching the end of their usefulness as the drugs of choice for the treatment of gonococcal infections in Surabaya. While the susceptibilities of N. gonorrhoeae to cephalosporins (ceftriaxone, cefixime, and cefoxitin) and fluoroquinolones (ciprofloxacin and ofloxacin) are universal, these drugs have not been used because they are more expensive in Indonesia than thiamphenicol. We conclude that Surabaya had the highest reported rate of penicillin and tetracycline resistance among the Southeast Asian countries and that cephalosporins or fluoroquinolones should be reasonable alternatives for the treatment of gonorrhea in this locale.